Study on consumption of fast food among medical students of IGIMS, Patna - Shree, Vijay; Prasad, R. R.; Kumar, Sanjay; Sinha, Setu; Choudhary, Sanjay Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Fast food culture is a vigorously uprising trend among the youngsters and medical students are no exception to it. Stressful life due to increased study load negatively influences the food choices of medical students. Hence the present study was undertaken with objectives to figure out the prevalence of fast food consumption among medical students, to study the fast food consumption pattern by the medical students and to explore various factors contributing to fast food consumption by the students. Methods: A cross sectional study was done among 120 undergraduate medical students of IGIMS, Patna for a period of 6 months. Data collection was done using pre-tested structured questionnaire and was analysed using SPSS latest version. Results: The study showed that all the respondents consume fast food sometime or the other and the knowledge of fast food was almost universal among the medical students. Most of the students (48.3%) were taking fast food as an alternative to dinner, 32 (26.6%) as evening snack and 26 (21.6%) as an alternative to lunch. Most preferred beverage was carbonated drinks (56.6%) while most preferred fast food was pizza (45%). 75.6% students were taking fast food 1-2 times a week. Reasons for consumption of fast food were mainly- eating in company (58.3%) and taste factor (55%). Conclusions: Despite of a majority (88.3%) being aware of the fact that consuming fast food leads to many diseases and disability, all the subjects continue to consume fast food, mostly due to reasons of taste, company and to avoid wastage of time.